Reforming Indian electoral process - Sanjay Kumar (2002)
The attempt to reform the electoral system is a welcome move. However, the current proposals on candidates' disclosures of various kinds do not appear to be well-constructed and the bill includes ambiguities which are open to misinterpretation. It is perhaps more important immediately to strengthen the system of preparing electoral rolls and allowing public access to them. - Reproduced.
Keywords: Electoral systems - India; Electoral systems